2019
DOI: 10.4236/nm.2019.103020
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-Inflammatory Activity of Total Crude Leaf Extract of <i>Phytolacca dodecandra</i> in Wistar Albino Rats

Abstract: Background: Pain is a common problem encountered in daily life among humans and animal and it is commonly managed conventionally using modern medicines and traditionally by use of medicinal plants. Phytolacca dodecandra is a common herb in Uganda, used traditionally to alleviate pain and inflammatory conditions. However, its activity in alleviating pain and inflammatory diseases has not been fully scientifically evaluated. Aim of Study: To evaluate the analgesic and anti-inflammatory activity of total crude le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Moreover, PKC and MAPK also stimulate the exudation and activation of several pro-inflammatory cytokines and mediators of inflammatory mechanisms ( Rodrigues et al, 2016 ; Da Silva et al, 2018 ). Both indomethacin and the cyclooxygenase (COX) pathway are frequently effective in an experimental model and are involved in medical practice; they are responsible for reducing inflammation and relieving pain by impeding the production of the prostaglandins ( Nakalembe et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PKC and MAPK also stimulate the exudation and activation of several pro-inflammatory cytokines and mediators of inflammatory mechanisms ( Rodrigues et al, 2016 ; Da Silva et al, 2018 ). Both indomethacin and the cyclooxygenase (COX) pathway are frequently effective in an experimental model and are involved in medical practice; they are responsible for reducing inflammation and relieving pain by impeding the production of the prostaglandins ( Nakalembe et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study's findings demonstrated that, when compared to the control and extract groups, the reaction time in the formalin-only treated rats (group 2) dramatically decreased. Reduced pain behaviour reaction times are a sign that an animal is experiencing extreme or increased pain [15].…”
Section: B Pain Behavioral Values Of Study Animals After 14 Days Of E...mentioning
confidence: 99%
“…Though P. dodecandra has been reported to be traditionally used to treat dog bites/rabies in Ethiopia (Meresa et al 2017) and in DRC (Beressa et al 2020), this is the first time to be cited for the management of dog bites in Uganda. Other traditional uses in Uganda include; the management of skin disorders, inducing abortion, (Nakalembe et al 2019), and cleansing clothes (Beressa et al 2020). In other parts of the world, P. dodecandra is used traditionally in treating malaria, sore throat, rabies, tuberculosis, asthma in DRC, epilepsy in Tanzania (Beressa et al 2020), gonorrhea, and helminthiasis in Ethiopia (Tahir, et al 2023).…”
Section: Medicinal Plant Species Used Traditionally To Manage Dog Bitementioning
confidence: 99%